Mitochondrial fission factor drives an actionable metabolic vulnerability in multiple myeloma - Maria Eugenia Gallo Cantafio; Ilenia Valentino; Roberta Torcasio; Ludovica Ganino; Claudia Veneziano; Pierpaolo Murfone; Maria Mesuraca; Ida Perrotta; Federico Tallarigo; Valter Agosti; Carmela De Marco; Teresa Pasqua; et al. (Haematologica)
Proliferating multiple myeloma (MM) cells in the bone marrow fluctuate across various metabolic states to resist cancer treatments. Herein, we investigate how mitochondrial dynamics, which controls mitochondrial fitness via coordinated fission and fusion events, shapes MM cell metabolism impacting growth, survival and drug sensitivity. We identify MFF (Mitochondrial Fission Factor), a pivotal driver of mitochondrial fragmentation, as being highly expressed in MM plasma cells bearing cytogenetic abnormalities predicting poor clinical outcome. In preclinical models, MFF selective inhibition via multiple RNAbased strategies (shRNAs, siRNAs or LNA gapmeR ASOs) reduces MM cell growth both in vitro and in vivo, enabling adaptive metabolic responses consistent with the induction of glycolysis and the inhibition of lactate-mediated OXPHOS. We also demonstrate that lactate supplementation, as well as clinically relevant drugs promoting lactate accumulation, such as AZD3965 and Syrosingopine, trigger MFF-dependent metabolic changes, enhancing the sensitivity of MM cells to strategies targeting mitochondrial fission. Finally, we highlight a novel lactate-MFF axis involved in proteasome inhibitor resistance, and show that combining AZD3965 or Syrosingopine with bortezomib results in synergistic anti-MM activity along with MFF down-regulation. Collectively, these data point to MFF-dependent mitochondrial fragmentation as a key metabolic hallmark of MM, providing a framework for the development of novel therapeutic strategies targeting mitochondrial dynamics and harnessing the metabolic plasticity of malignant plasma cells.